A Strategy to Boost H2 Generation Ability of Metal–Organic Frameworks: Inside‐Outside Decoration for the Separation of Electrons and Holes. Issue 4 (29th January 2018) - Wang, Yang; Ling, Lianjie; Zhang, Wei; Ding, Kejian; Yu, Yu; Duan, Wubiao; Liu, Bo
Abstract: Inhibiting the recombination of electron and holes plays an essential role in photocatalytic process, particularly for metal–organic frameworks (MOFs), which had long been anticipated as high‐efficient photocatalysts. Herein, we introduce a new strategy to make efficient separation of electrons and holes for the MOF‐based photocatalyst, UiO‐66‐NH2 . At first, encapsulation of Pt nanoparticles (NPs) into UiO‐66‐NH2 (Pt@U6N) to shorten the electrons transport distance inside of MOF crystals, then using graphene oxide to wrap the external surface of Pt@U6N to facilitate the electrons transfer on the surface. The designed structure was found to possess superior H2 ‐generation ability compared to only inside or outside decorated samples, highlighting that the enhanced property strongly correlates with the inhibited recombination of electrons and holes by the inside/outside modification strategy. These findings suggest a synergistic effect of Pt NPs and graphene oxide on UiO‐66‐NH2 and reveal a new modification strategy to enhance the catalytic activity of the photocatalysts. Abstract : Inner and outer beauty : Pt nanoparticles are used to decorate the inside of metal–organic frameworks and graphene oxide is used to decorate its outer surface. The inside/outside decoration strategy creates a synergistic effect and results in increased activity and stability for photocatalytic H2 production.